1999
DOI: 10.1046/j.1432-1327.1999.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow‐binding and competitive inhibition of 8‐amino‐7‐oxopelargonate synthase, a pyridoxal‐5′‐phosphate‐dependent enzyme involved in biotin biosynthesis, by substrate and intermediate analogs

Abstract: 8-Amino-7-oxopelargonate synthase catalyzes the first committed step of biotin biosynthesis in micro-organisms and plants. Because inhibitors of this pathway might lead to antibacterials or herbicides, we have undertaken an inhibition study on 8-amino-7-oxopelargonate synthase using six different compounds. d-Alanine, the enantiomer of the substrate of this pyridoxal-5 H -phosphate-dependent enzyme was found to be a competitive inhibitor with respect to l-alanine with a K i of 0.59 mm. The fact that this inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 22 publications
(32 reference statements)
3
18
1
Order By: Relevance
“…Contrary to our finding of D-alanine being a substrate for the M. tuberculosis KAPA synthase, it has previously been reported to act as a competitive inhibitor for the B. sphaericus enzyme (12). Indeed, addition of D-alanine resulted in inhibition of the M. tuberculosis KAPA synthase-catalyzed reaction between L-alanine and pimeloyl-CoA.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to our finding of D-alanine being a substrate for the M. tuberculosis KAPA synthase, it has previously been reported to act as a competitive inhibitor for the B. sphaericus enzyme (12). Indeed, addition of D-alanine resulted in inhibition of the M. tuberculosis KAPA synthase-catalyzed reaction between L-alanine and pimeloyl-CoA.…”
Section: Discussioncontrasting
confidence: 99%
“…3, A and B) with dissociation constants, K d of 1.93 Ϯ 0.28 mM and 12.49 Ϯ 1.80 mM for L-and D-alanine, respectively. These values are in agreement with those obtained for the corresponding E. coli (7) and B. sphaericus enzymes (12), which also exhibit an increased affinity for D-alanine in the presence of pimeloyl-CoA. However, in contrast to both these enzymes (7,12), addition of increasing concentrations of D-alanine to M. tuberculosis KAPA synthase in the presence of saturating concentrations of pimeloyl-CoA, resulted in the appearance of an absorption band centered at 532 nm, apart from the formation of external aldimine (Fig.…”
Section: Interaction With L-and D-alaninesupporting
confidence: 91%
See 2 more Smart Citations
“…We have performed molecular genetic dissection using reverse genetics of antisense approach to identify AtKAPAS gene encoding KAPA synthase in the pathway of biotin biosynthesis and to characterize the phenotypic consequences of loss-of-function mutations (Hwang et al, 2003;. Many researchers have investigated the KAPAS in microorganisms and the most of these reports were focused on the biosynthesis in microorganisms (Eisenberg and Star, 1968), purification and characterization (Ploux 1992, Stoner andEisenberg, 1975a;1975b), crystal structure (Alexeev et al, 1998, Kack et al, 1999, binding and kinetics (Ploux et al, 1999), point mutation (Andrew et al, 2002), and stereospecificity (Vikrant et al, 2006). Among them, Ploux et al (1999) reported that the KAPAS catalyzes the first committed step of biotin biosynthesis in micro-organisms and plants, and suggested that the inhibitors of this pathway might lead to antifungal or herbicide agents.…”
Section: Discussionmentioning
confidence: 99%